ANALYSIS AND COMPARISON OF CURRENT DIADYNAMICS ISOLATED AND THE ASSOCIATION WITH IONTOPHORESIS, APPLIED IN FEMALE STUDENTS WITH LOW-BACK-PAIN (Fiep Bulletin - online, 2013)
The iontophoresis is a noninvasive technique of administering drugs in ionic form to the body, which uses electric current, with the greatest satisfaction when compared to passive percutaneous absorption. The current Diadynamics have analgesic effects and galvanic components essential to the use of iontophoresis. The low-back-pain, increasingly present in the world brings associations of inflammatory processes and context about pain because of several causes. The research aimed to analyze and compare the effects of currents Diadynamics isolated and associated with iontophoresis in low back pain of female students. 12 females students aged between 18 and 26 years participated in the survey complaining of back pain for more than a year. Participants were initially assessed to various criteria, next to which was enforced a scale of pain intensity and then reapplied and compared with the initial results. The sample was divided randomly into two groups, Group 1 received the memorandum of Current Diadynamics alone, Group 2 Current Diadynamics associated with iontophoresis with dexamethasone 0.1%, and held seven sessions. The equipment used for applying the current was the USS ENDOFHASYS-0503, mark KLD Biosistemas. The intensity of this was in accordance with the patient's subjective feeling. The data were statistically analyzed by the program Microsoft Excel 2003, and for variables, non-parametric tests for signs of Wilcoxon test and U. of Mann Whitney, where p = 0.05 determining significance, from the program SPSS for Windows 13.0. The results were significant for both treatments, GROUP 1 p = 0.02 and Group 2 p = 0.02, noting an improvement of 21% of treatment group 2 than group 1. It appears that both the current Diadynamics alone, as associated with iontophoresis brought significant improvement in back pain for female students.
Keywords: Diadynamics Current; Iontophoresis; lumbago